Control strategies and co-design of networked control systems : considering time delay effects /: considering time delay effects. ([2019]) - Benítez-Pérez, Héctor; Ortega-Arjona, Jorge L; Méndez-Monroy, Paul E; Rubio-Acosta, Ernesto; Esquivel-Flores, Oscar A
No abstract available